The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1038/s41419-022-04523-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the pathogenesis of psoriasis: from keratinocyte perspective

Abstract: Psoriasis is a complex long-lasting inflammatory skin disease with high prevalence and associated comorbidity. It is characterized by epidermal hyperplasia and dermal infiltration of immune cells. Here, we review the role of keratinocytes in the pathogenesis of psoriasis, focusing on factors relevant to genetics, cytokines and receptors, metabolism, cell signaling, transcription factors, non-coding RNAs, antimicrobial peptides, and proteins with other different functions. The critical role of keratinocytes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(153 citation statements)
references
References 147 publications
(180 reference statements)
2
149
0
2
Order By: Relevance
“…Psoriasis is an autoimmune disease mediated by overactive IL17 secreting type 17 T-cells (such as Th17 and Tc17) and defective negative regulatory networks (such as dysfunctional Tregs). Many researchers have focused on immune-related factors in the development of psoriasis, but haveignored the cell-fate transition of hyperproliferative keratinocytes themselves [31]. As part of this work, scRNA-seq analysis of psoriasis and control skin-derived cells were performed to identify the cell fate transition of nonimmune subsets (Additional file 1: Fig.…”
Section: Imbalances Of Ferroptosis and Pyroptosis Involved In The Dev...mentioning
confidence: 99%
“…Psoriasis is an autoimmune disease mediated by overactive IL17 secreting type 17 T-cells (such as Th17 and Tc17) and defective negative regulatory networks (such as dysfunctional Tregs). Many researchers have focused on immune-related factors in the development of psoriasis, but haveignored the cell-fate transition of hyperproliferative keratinocytes themselves [31]. As part of this work, scRNA-seq analysis of psoriasis and control skin-derived cells were performed to identify the cell fate transition of nonimmune subsets (Additional file 1: Fig.…”
Section: Imbalances Of Ferroptosis and Pyroptosis Involved In The Dev...mentioning
confidence: 99%
“…It is characterized by an abnormal cell cycle of epidermal cells that leads to epidermal hyperproliferation and altered maturation of these cells, vascular alterations, and inflammation [1,2]. The pathogenesis of psoriasis is highly complex, that includes keratinocytes, inflammatory cells, pro-inflammatory cytokines, and growth factors [3,4]. Recently published data have delivered new understandings of the cellular and molecular pathways involved in the pathogenesis of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of keratinocytes to resist apoptosis plays an important role in disease pathogenesis. Furthermore, keratinocytes produce inflammatory cytokines such as TNF-α, IL-23, and IL-17 together with infiltrated immune cells, which trigger the vicious cycles of the disease [42]. Preclinical pharmacology studies demonstrated that piclidenoson inhibited the proliferation of human keratinocytes (HaCat cells).…”
Section: Piclidenoson In Psoriasismentioning
confidence: 99%